How rising ICE activity influences the childcare workforce - Erkmen G. Aslim; Janet Currie; Chris M. Herbst; Erdal Tekin (Proceedings of the National Academy of Sciences, 2026)
Immigrants play a critical role in the US childcare workforce, yet little is known about how immigration enforcement shapes employment in this essential sector. We study how the sharp escalation in community-based Immigration and Customs Enforcement (ICE) activity following President Trump’s inauguration in early 2025 affected childcare employment in the United States. Monthly data from the Current Population Survey are linked to compiled state-level ICE arrest records from September 2023 through September 2025, to ask how changes in enforcement intensity influence employment across childcare settings that differ in regulation and visibility. We find that increased ICE activity led to significant declines in employment among foreign-born women, with effects concentrated in center-based settings that are highly regulated and publicly visible. At the same time, employment in private household childcare increased, consistent with a reallocation toward less visible and less formal arrangements rather than a complete exit from the sector. These effects strengthened markedly after early 2025, a period characterized both by a sharp rise in nonprison ICE arrests and heightened public attention to immigration enforcement. Among native-born women, employment responses are limited in magnitude and confined to a limited number of specific care settings, providing little evidence of broad substitution for foreign-born workers. Overall, the results show that immigration enforcement reshapes not only the size but also the structure of the childcare workforce, with important potential implications for childcare access, labor markets, and families.